Freehand versus Grid-Based Transperineal Prostate Biopsy: A Comparison of Anatomical Region Yield and Complications. Issue 4 (8th October 2021) - Urkmez, Ahmet; Demirel, Cihan; Altok, Muammer; Bathala, Tharakeswara K.; Shapiro, Daniel D.; Davis, John W.
Abstract : Purpose: The freehand (FH) technique of transperineal prostate biopsy using commercialized needle access systems facilitates a reduction in anesthesia requirements from general to local or local/sedation. We sought to compare the efficacy and complication rates of the FH method with those of the standard grid-based (GB) method. Materials and Methods: The GB method was performed from 2014 to 2018, and the updated FH technique was performed from 2018 to 2020, yielding comparative cohorts of 174 and 304, respectively. Results: The FH and GB techniques demonstrated equivalent yields of ≥Gleason grade group (GGG)-2 prostate cancer (PCa). The FH group had a significantly higher mean number of cores with ≥GGG-2 PCa involvement (p=0.011) but a significantly lower mean number of biopsy samples (p <0.01). The urinary retention rate of the GB group (10%) was significantly higher than that of the FH group (1%; p <0.01). The rates of ≥GGG-2 PCa involvement in the anterior (GB, 31%) and anteromedial (FH, 22%) sectors were higher than those in other sectors (range, 0%–9%). For multiparametric magnetic resonance imaging, the rate of ≥GGG-2 PCa detection in the anteromedial prostate (23%) was nearly half that in other locations (range, 38%–55%). Conclusions: Compared with GB transperineal biopsy, FH transperineal biopsy demonstrates an equivalent cancer yield with no risk of sepsis, a significantly reduced risk of urinary retention, and reduced anesthesia needs. The higher number of cores with ≥GGG-2 PCa involvement in the FH group suggests that FH transperineal biopsy can sample the prostate better than GB-transperineal biopsy can.